EVIDENCE-BASED AND INTELLIGENCE-LED POLICING IN SMALL ARMS AND LIGHT WEAPONS CONTROL IN THE REPUBLIC OF NORTH MACEDONIA – A Review of the National strategy for SALW control in accordance with the National action plan 2022–2024 - Leta M. Bardjieva; Dimitriev Emil (Филозофски факултет, 2025)
The purpose of this paper is to present the efforts and commitment of the Republic of North Macedonia in the joint contribution toward peace and security, as stated in the Sofia Declaration from 2018 and the UN 2030 Agenda for Sustainable Development, specifically in relation to the 16th of the sustainable development goals committed to peace, justice and strong institutions. The paper elaborates the prescribed activities for control of small arms and light weapons (SALW), emphasising the Action plan from the National Strategy for Small Arms and Light Weapons control of the Republic of North Macedonia 2022–2024, with the method of qualitative and quantitative review of the Goal 2 of the Strategy regarding the evidence-based and intelligence led policies and practices for SALW control. The findings in this paper emphasize the observations of the declarative efforts, in particular in sub-goals 2.2, 2.3 and 2.4 of the same Strategy, referring to their operationalization. Through analysis of the implementation of relevant legislation and institutional practices for the prevention of the misuse of SALW, monitoring of crime related to SALW, improving national capacities and institutionalizing the analysis of firearms data with the introduction of the mandatory operational information framework, providing exchange of operational and strategic information, data, intelligence products, as well as evidence material, conduction of impact studies and operationalization and linkage with the national contact weapons point, thereby contributing to enhanced stability, security and development in Southeast and Eastern Europe. The limitations of this paper are the lack of nationally available data for the successfulness of the implementation of the Strategy
Keywords: small arms and light weapons, policing, strategy, intelligence, control, management